An encyclopedia of gardening for colored children - Kincaid, Jamaica (Farrar, Straus and Giroux, 2024)
"In this modern-day abecedarium, Jamaica Kincaid shares her deep knowledge of plant history and nomenclature while writing about the intersections of the plant world with history, race, mythology, colonial appropriation, and independence. Accompanied by vivid, powerful illustrations by Kara Walker"--